Case Report: Medial Sural Nerve Entrapment Neuropathy - Mahmoud Farzan; Seyyed Mohammad Javad Mortazavi (University of Social Welfare and Rehabilitation Sciences, 2002)
Chronic calf pain may have various etiologies including stress fracture, chronic compartment syndrome, accessory Soleous muscle, and muscle sprains. An uncommon cause of chronic calf pain is entrapment neuropathy. Because entrapment neuropathies are uncommon, they are often under diagnosed. A 15-year-old adolescent developed progressive calf pain 10 months before his presentation. Physical examination and paraclinical studies revealed no abnormality and electrodiagnostic study was reported as normal. 2 months nonoperative the superficial Sural aponeurosis treatment and one surgical intervention were failed. Reexamination was revealed positive Tinel's sign and paresthesia in distribution of the Sural nerve. Surgical exploration revealed entrapment of the medial Sural cutaneous nerve localized in the passage of the nerve resulted in completeresolution of symptoms and full recovery. Several location for entrapment of the Sural nerve were reported, but we couldn't found any report in English language literature about Sural nerve entrapment in the superficial Sural aponeurosis in no athletics.